Neuroprotective effect of (-)-tetrahydropalmatine in Japanese encephalitis virus strain GP-78 infected mouse model. (January 2018) - Lixia, Huang; Jun, Chen; Song, Hu; FaHu, Yuan; Jinwen, Tu
Abstract: Japanese encephalitis virus (JEV), known to affect children, is a major cause of severe encephalopathy. Its prevalence has been percolated over wider regions of Southern Asia. JEV is associated with neurodegeneration, severe inflammation, increased oxidative stress and elevated levels of stress linked proteins. Four groups of 15 mice each (4–5 weeks old BALB/c mice of either sex) was used for the study. Mice were intravenously infected with lethal dose of 3 × 10 5  pfu of JEV, followed by mortality after 8 days. On the next day and onwards, the animals were administered intraperitonially with (-)-tetrahydropalmatine (LTHP) solution (0.1 mg/mL in PBS) for the next 7 days. Animals exhibited protection against JEV infection, after being administered with LTHP. Reduction in levels of, viral population, caspase-2 expression, reactive oxygen and nitrogen species, microglial cells and proinflammatory mediators, stress linked protein molecules and neuronal apoptosis was exhibited in JEV infected animals treated with LTHP. The effects produced by the administration of LTHP indicated its possible use to treat JEV in mouse model. Potential to reduce viral count in brain and subsequent neuronal apoptosis, reduction in mediators of inflammation and oxidative stress, strictly advocate the use of LTHP for treatment of JEV. Thus, the present investigation indorses LTHP as a potentially strong drug candidate for the treatment of JEV infection due to its neuroprotective, anti-inflammatory, antiviral and anti-oxidative effect.